Optimizing students’ practical skills through project-based learning: case study in vocational high schools - Dzulkurnain, Mohammad Iskandar; Aminuddin, Afrig; Hammood, Waleed A.; Abdullah, Khairul Hafezad; Alam Miah, Mohammad Badrul (International Journal of Evaluation and Research in Education (IJERE), 2024)
Competition in the global era requires graduates from vocational schools to be more skilled in hard and soft skills to adapt to the industrial world. Adaptation of vocational education institutions to the industrial world is vital; thus, they can continuously update the skills of their graduate candidates. Hence, this research aims to describe the implementation of the Center of Excellence curriculum and project-based learning in a vocational high school as a form of school adaptation to the development of the industrial world in the 21st century. This research was included in a qualitative research design adopting a case study. The research respondents consisted of vocational high school residents in Central Java. Data was collected through interview techniques and observations and then analyzed interactively and descriptively. The research results then reported that the school was fully committed to implementing the Center of Excellence curriculum regarding teaching human resources and learning facilities. The project-based learning process also seemed to run optimally. Students could accept it, considering that project-based learning was implemented because it was an adaptive model to accommodate 21st century competencies. However, there is still room for improvement and optimization in order to effectively implement this operational curriculum and enhance students' ability to acquire 21st century skills.